2014
DOI: 10.1159/000360702
|View full text |Cite
|
Sign up to set email alerts
|

Low Adherence to Upfront and Extended Adjuvant Letrozole Therapy among Early Breast Cancer Patients in a Clinical Practice Setting

Abstract: Objective: The aim of this study was to investigate the prevalence and causes of early discontinuation and non-adherence to upfront and extended adjuvant letrozole therapy in breast cancer patients. Methods: Adherence was assessed using medical charts and longitudinal pharmacy records of 609 patients who initiated adjuvant letrozole between January 2002 and April 2011. A Cox proportional hazards regression model was adopted to identify potential predictors of non-adherence. Results: The overall adherence rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 38 publications
(55 reference statements)
1
16
0
Order By: Relevance
“…Nine studies showed lower odds of adherence for women under the age of 40/50 years, 9 , 23 , 28 , 31 , 33 , 34 , 38 , 39 , 58 one study found the opposite, 59 and three studies showed no significant effects. Six studies found that older women (>65/75 years) were less likely to be adherent.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Nine studies showed lower odds of adherence for women under the age of 40/50 years, 9 , 23 , 28 , 31 , 33 , 34 , 38 , 39 , 58 one study found the opposite, 59 and three studies showed no significant effects. Six studies found that older women (>65/75 years) were less likely to be adherent.…”
Section: Resultsmentioning
confidence: 92%
“…The majority of clinical factors showed no consistent associations with adherence or showed mixed results (eg, tumor size, previous chemotherapy and lymph node status). Switching between HTs was associated with decreased adherence in seven studies 23 , 28 , 33 37 and increased adherence in three studies. 8 , 38 , 39 The majority of articles did not specify the direction of switching between medications.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Studies show that by the fifth year of treatment, up to 50% of women have discontinued (Hadji et al ., ; Owusu et al ., ). Adherence rates range over the course of treatment from 41 to 88% (Murphy, Bartholomew, Carpentier, Bluethmann, & Vernon, ) and fall to 50% by the fifth year of treatment (Lee et al ., ; Partridge, ). As non‐adherence and non‐persistence have similar effects on clinical outcomes, they will both be referred to as ‘(non)‐adherence’ when discussing the implication of the research.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Limited evidence suggests early discontinuation of hormonal treatments is associated with older age 11,12 and adverse effects 13,14 and usually occurs within the first year, but may also occur in subsequent years. 15,16 However, underlying reasons for these decisions remain poorly understood. 13,17 Because AIs are oral medications that are self-administered in the home setting and started during the transitional survivorship period, 18,19 we wanted to understand what factors are associated with persistence and how these medications fit into the broader life context of older breast cancer survivors from the perspectives of the women themselves.…”
Section: Introductionmentioning
confidence: 99%